2012
DOI: 10.5539/ass.v8n13p51
|View full text |Cite
|
Sign up to set email alerts
|

Social Demographic Factors That Influence Transformational Leadership Styles among Top Management in Selected Organizations in Malaysia

Abstract: Literatures have not adequately discusses the influence of demographic variables on Leadership styles among top management in Malaysian organizations. Hence, the overall aim of the study was to investigate if there is significant difference between social demographic factors and transformational leadership style among top management in selected organizations in Malaysia. Data was collected through an instrument of leadership styles known as the MLQ to test the dependent variable (Transformational leadership). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…This finding may be due to the fact that the Philippines' education system is undergoing changes at every level, hence it seems that more people from within and outside Manila are becoming more aware of the relationship between leadership style and faculty and student performance. The findings of this study are consistent with those of previous studies (Mohammed, Othman, & Silva, 2012;Jones & Bekhet, 2015;Francis, 2017). We found that gender was associated with transactional leadership, and that transactional leadership was practiced more by female leaders.…”
Section: (Ii) Resultssupporting
confidence: 93%
“…This finding may be due to the fact that the Philippines' education system is undergoing changes at every level, hence it seems that more people from within and outside Manila are becoming more aware of the relationship between leadership style and faculty and student performance. The findings of this study are consistent with those of previous studies (Mohammed, Othman, & Silva, 2012;Jones & Bekhet, 2015;Francis, 2017). We found that gender was associated with transactional leadership, and that transactional leadership was practiced more by female leaders.…”
Section: (Ii) Resultssupporting
confidence: 93%
“…Elemen situasi penting kerana berupaya menghalang dan membenarkan perlaksanaan amalan kepimpinan distributif (Spillane, 2006). Faktor demografi didapati berupaya menentukan tingkah laku kepimpinan dalam organisasi (Mohammed, Othman & D'Silva, 2012) dan menurut model kepimpinan distributif Spillane (2006) adalah alat bagi mengamalkan kepimpinan distributif.…”
Section: Model Kepimpinan Distributifunclassified
“…Responden kaji diperlukan untuk memberi maklumat mengenai faktor demografi mereka. Faktor demografi penting kerana berperanan dalam menentukan tingkah laku kepimpinan dalam organisasi (Mohammed, Othman & D'Silva, 2012). Kedua-dua instrumen soal selidik iaitu PDLP dan PLCA-R dan faktor-faktor demografi digabungkan bagi memudahkan proses mengagihkan borang soal selidik kajian kepada responden kajian, seperti yang ditunjukkan di dalam Lampiran A. Bahagian A adalah faktor-faktor demografi, bahagian B adalah persepsi amalan kepimpinan distributif manakala bahagian C adalah persepsi amalan komuniti pembelajaran professional.…”
Section: Instrumen Soal Selidikunclassified
“…Kabeer. AM et al [3], leadership is the process of influencing others so that they understand and agree on the work to be done and how to do it effectively, is the process of creating create favorable conditions for individuals and groups to strive to achieve the goals of the organization. Warren Bennis [1], leadership is a socially influential process of seeking the voluntary participation of subordinates to best realize the organization's goals.…”
Section: The Concept Of Leadershipmentioning
confidence: 99%